Implementasi penguatan Pendidikan Karakter melalui pembelajaran Tematik berbasis Kearifan Lokal di kelas IV SD Muhammadiyah 1 kota Malang - Ima Wahyu Putri Utami (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The purpose of this study is to 1) describe the implementation of strengthening character education through thematic learning based on local wisdom in Muhammadiyah 1 Elementary School in Malang City, 2) describe the supporting factors and inhibiting factors in the implementation of strengthening character education through thematic learning based on local criteria in grade IV SD Muhammadiyah 1 Malang City, 3) describes the solution of the inhibiting factor in the implementation of strengthening character education through thematic learning based on local wisdom in grade IV SD Muhamamdiyah 1 Malang City. This research uses qualitative research. The reasoning method used is interviews, observation and documentation. The results of this study indicate that the strengthening of character education at Muhammadiyah 1 Elementary School in Malang City is carried out through thematic learning based on Malang local wisdom. The wisdom of Malang City which is used in thematic learning is through batik activities, and traditional games. From character batik learning that can be developed in students is diligence and accuracy. Whereas from the traditional game of sarong racing can be developed the character of cooperation.